The Essence of Human Right to Health: An Analytical Study in Light of Saudi Law - Maysaa Ziad Bawazir (International Journal of Law Research and Studies, 2025)
The right to health is defined as every individual's entitlement to enjoy the highest attainable standard of physical, mental, and psychological well-being. This right extends beyond the mere provision of healthcare services to encompass the broader concept of a healthy life, ensuring both preventive and curative measures. It includes the essential determinants of health, such as access to clean drinking water, adequate nutrition, housing, and healthy working and environmental conditions. This study addresses the nature of the right to health through a descriptive examination of its scope and an analytical review of the legal texts governing it within both national legislation and international instruments. The first section of this paper aims to define the right to health from linguistic and terminological perspectives, followed by a legal definition of the right. It then explores the regulatory foundations of the right to health at the national level, referencing the Basic Law of Governance and relevant regulations, and at the international level, through conventions and treaties. The second section discusses preventive oversight mechanisms for safeguarding the right to health, as well as judicial oversight.The study concludes that the right to health is a comprehensive entitlement for every individual to enjoy the highest attainable standard of physical, mental, and psychological health, encompassing both prevention and treatment. This right is firmly grounded in the Basic Law of Governance and in international conventions and agreements. The Saudi legal framework guarantees individuals the right to seek judicial remedy—both general and administrative—in cases of infringement upon their right to health.In its final recommendations, the paper calls for amending the Health Law to include explicit provisions defining the right to health, outlining mechanisms for its protection, and stipulating penalties for violations. It also emphasizes the importance of enhancing the educational and research role of the Human Rights Commission by organizing regular national and international conferences and workshops that highlight the Kingdom’s efforts in protecting this right and promote awareness of its safeguarding mechanisms.
Keywords: Human Rights; Right to Health; Basic Law of Governance; International Conventions; Public Health